2016
DOI: 10.1161/strokeaha.115.012130
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Embolic Events in Hypertrophic Cardiomyopathy

Abstract: Background and Purpose-Stroke and systemic embolic events are known to occur as complications of hypertrophic cardiomyopathy (HCM), and these complications are more common in patients with accompanying atrial fibrillation (AF). The diagnosis of AF is sometimes difficult, however, and it is possible that subclinical asymptomatic paroxysmal episodes or a first episode of AF in patients without previously documented AF may lead to embolic events. We investigated the prevalence of embolic events in patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…After screening titles and abstracts, we obtained 44 articles for full-text reviewing. Finally, six studies were eligible for inclusion ( Figure 1) (7,(13)(14)(15)(16)(17).…”
Section: Literature Searchmentioning
confidence: 99%
“…After screening titles and abstracts, we obtained 44 articles for full-text reviewing. Finally, six studies were eligible for inclusion ( Figure 1) (7,(13)(14)(15)(16)(17).…”
Section: Literature Searchmentioning
confidence: 99%
“…9,10 It is worth noting that these recommendations are based mainly on expert consensus and several relatively small observational studies as there are currently no prospective randomized controlled trials (RCTs) on the subject to date. 1,5,7,[11][12][13][14][15][16][17][18][19][20][21] review, these outcomes were compared between the different AC strategies when available. For the comparisons of AC versus no AC or DOACs versus VKAs, thromboembolic events were excluded if they occurred in association with or prior to the initial episode of AF as there was no opportunity for a treatment strategy to be chosen.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, the evidence to use anticoagulant to prevent cardioembolic stroke in hypertrophic cardiomyopathy with normal sinus rhythm is not known. Haruki et al (2016) in hospital-based observational study demonstrated older age at diagnosis and enlarged left atrial dimension of more than 47 mm were the possible risk factors for embolic events in patients with hypertrophic cardiomyopathy without documented atrial fibrillation. 9 However, our patient had normal size left atrium (36mm).…”
Section: Discussionmentioning
confidence: 95%